2021
DOI: 10.4236/ss.2021.126019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Digestive Emergencies in Two Hospitals in Douala (Cameroon)

Abstract: Background: Gastrointestinal tract (GIT) surgical emergencies represent a significant amount within surgical pathologies, in Africa and throughout the world. Our study was aimed to assess the etiological, therapeutic and prognostic aspects of GIT surgical emergencies in patients from two hospitals in Douala, Cameroon. Patients and Method: A longitudinal prospective study was conducted from December 2018 to May 2019, including 203 patients of all ages and both sexes who presented with a GIT surgical emergency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
3
1
0
Order By: Relevance
“…Abdominal surgical emergencies affect a heterogeneous group of people including all age groups and genders. Male predominance (male to female ratio = 1.4:1) was observed in this study which is in agreement with other studies in Africa, and even in the developed world [12,13,18,19]. The mean age was 47.4 years which is comparable with findings in South Africa reported by Rickard et al [8], in the USA reported by Purcell et al in Malawi [16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Abdominal surgical emergencies affect a heterogeneous group of people including all age groups and genders. Male predominance (male to female ratio = 1.4:1) was observed in this study which is in agreement with other studies in Africa, and even in the developed world [12,13,18,19]. The mean age was 47.4 years which is comparable with findings in South Africa reported by Rickard et al [8], in the USA reported by Purcell et al in Malawi [16].…”
Section: Discussionsupporting
confidence: 92%
“…The in-hospital delay from presentation to surgery was 8 hours (median). This compares favorably with other studies from Africa [12,22]. However, this is still very high when compared with findings from developed countries.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations